Rousseau e a formação do homem autônomo - Silva, Geraldo Márcio da (2020)
This work is a theoretical research, investigates the formation of Emile in Jean-Jacques Rousseau and the reasons that led him to form him outside society. To this end, in the first chapter we will address the reasons for the refusal to form man in the instituted society, the constitution of man in the state of nature, which made him leave the state of nature, the acquisition of a new way of life, the creation of the marital status and Emile and the refusal of society. In the second chapter there will be a study of the child's preparation to be educated against positive education. For that, we investigate the education of society, the social man, the impossibility of training man in society, what formation he proposes, what he refuses, to understand the educational project proposed by him. In the third chapter we will deal with negative education, the negative education phases and the formation of the Emile. The work Emile, or on education is the main reference, supporting works: Essay on the Origin of Languages, Discourse on the Arts and Science (First Discourse), Discourse on the Origin and Basis of Inequality Among Men (Second Discourse), The Social Contract and Julie, or the New Heloise. Rousseau prepares the child to be educated against positive education, one that anticipates knowledge and disrespects the stages of formation. Thus, what it reproduces is not internalized because it does not have the intellectual maturity to understand. Thus, the harm these teachings cause to her intellectual development is nothing but futility. This education is incapable of autonomous man, so he thinks of negative education, one that conserves human nature and respects the phases of the child's formation, allowing him to learn to meet his own needs. In this way, the body gradually acquires the strength necessary to overcome natural obstacles. Thus, human nature is kept away from social habits and customs. This is the formation of the autonomous man, one who has the balance between strength and need and is complete at any time in life.